2014
DOI: 10.1111/jep.12216
|View full text |Cite
|
Sign up to set email alerts
|

Do violence dynamics matter?

Abstract: Dynamic pattern of violence, degree of violence non-linearity and optimal non-linearity correlated with several attitudinal/behavioural and clinical outcomes. Knowledge of violence dynamics may have applications when working with violent couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Current evidence suggests that symptoms of BPD are associated with IPV‐related PTSD, even after controlling for the severity of the interpersonal abuse (Kuijpers, van der Knaap, Winkel, Pemberton, & Baldry, ). These data bolster the observation that the clinical presentation of mental health symptoms is multifaceted in this population (Katerndahl, Burge, Ferrer, Becho, & Wood, ). Because PTSD and BPD symptoms are both common problems among women who have experienced IPV (Gobin, Iverson, Mitchell, Vaughn, & Resick, ; Kuijpers et al, ), greater focus on factors that influence or moderate the relationship between these conditions in this sample specifically is needed.…”
Section: Introductionsupporting
confidence: 74%
“…Current evidence suggests that symptoms of BPD are associated with IPV‐related PTSD, even after controlling for the severity of the interpersonal abuse (Kuijpers, van der Knaap, Winkel, Pemberton, & Baldry, ). These data bolster the observation that the clinical presentation of mental health symptoms is multifaceted in this population (Katerndahl, Burge, Ferrer, Becho, & Wood, ). Because PTSD and BPD symptoms are both common problems among women who have experienced IPV (Gobin, Iverson, Mitchell, Vaughn, & Resick, ; Kuijpers et al, ), greater focus on factors that influence or moderate the relationship between these conditions in this sample specifically is needed.…”
Section: Introductionsupporting
confidence: 74%
“…One hundred forty-three participants completed measures at baseline designed to assess background characteristics as well as factors that may affect the decision-making process. Prior work found that religious variables (Katerndahl, Burge, Ferrer, Becho, & Wood, 2015), awareness (Burke et al, 2001), depression and hope, childhood abuse, coping and violence appraisal, and partner's controlling behaviors contribute to violence dynamics and outcomes, including health care utilization (Katerndahl, Burge, Ferrer, Becho, & Wood, 2014a). In addition to demographics, we assessed religiousness using three scales (seven questions) from the Brief Multidimensional Measure of Religiousness/Spirituality (public religious activities, private religious activities, religious intensity; Fetzer Institute/National Institute on Aging Working Group, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Most of studies on battered women's cognitions rely on cross-sectional designs and omit the fact that cognitions may change over time (Solveig & Bjorkly, 2012). Few studies exist that adopted a longitudinal design (Bell, Goodman, & Dutton, 2007;Katerndahl, Burge, Ferrer, Becho, & Wood, 2014a, 2014b. When assessing cognitive distortion, adopting a longitudinal design is essential, because victims' retrospective answers on cognitive strategies may be shaped by the current state within the cycle of violence for reasons of cognitive consistency.…”
Section: Introductionmentioning
confidence: 99%